Branco Dominante : Amélia Toledo - Antonio Dias - Arcangelo Ianelli - Arthur Luis Piza - Athos Bulcão - Carmela Gross - Cristina Canale - Daniel Senise - etc. - de Mendonça, Casimiro Xavier (São Paulo : Galeria de Arte, 1992)
Toledo, Amélia ; Dias, Antonio ; Ianelli, Arcangelo ; Piza, Arthur Luis ; Bulcão, Athos ; Gross, Carmela ; Canale, Cristina ; Senise, Daniel ; Rosa, Dudi Maia ; Krajcberg, Frans ; Oiticica, Hélio ; Cmargo, Iberé ; Leirner, Jac ; Musatti, Jeanete ; Resende, José ; Catunda, Leda ; Leonilson ; Baravelli, Luiz Paulo ; Clark, Lygia ; Schendel, Mira ; Camargo, Sérgio ; Ohtake, Tomie ; tunga ; Duke Lee, Wesley
Branco Dominante, Galeria de Arte, São Paulo, de 7 de abril, às 21 horas, a 24 de abril de 1992
boek